2022
DOI: 10.15294/eej.v12i1.54521
|View full text |Cite
|
Sign up to set email alerts
|

The Realization of Formulaic Expressions in EFL Teacher-Student Classroom Interactions

Abstract: Formulaic expressions are essential for developing students' communicative competence to speak English naturally and fluently. This research aimed to determine how the EFL teachers and students used the five types of formulaic expressions in their classroom interactions. This study is discourse analysis, particularly conversation analysis, using a qualitative research approach. The research subjects were two teachers and thirty-one students from two different EFL classes in a private high school in Semarang. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…As an outcome, EFL learners can manage to have more control over their speaking ability in English. Furthermore, the findings of this research support Toub et al (2018) , Carpenter et al (2020) , Verzella (2020) , Indriyani et al (2022) , and Monica (2022) , which found that lexical bundles and formulaic language units aid second language learners in boosting their speech speed by allowing them to construct longer sentences.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As an outcome, EFL learners can manage to have more control over their speaking ability in English. Furthermore, the findings of this research support Toub et al (2018) , Carpenter et al (2020) , Verzella (2020) , Indriyani et al (2022) , and Monica (2022) , which found that lexical bundles and formulaic language units aid second language learners in boosting their speech speed by allowing them to construct longer sentences.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, high proficiency students produced more formulaic expressions. Likely, Indriyani et al (2022) investigated the Semarang EFL teachers and students use five types of chunks in their classroom communication. The study obtained thirty-three participants as the sample (two teachers and thirty-one students).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this category, lecturer has a simple question to students before learning and teaching will have been conducted. Khoiriyah and Mujiyanto (2022) describes classroom interaction is able to help teacher and students who are coming from EFL (English as Foreign Language) in mastering speaking. It means analysis of classroom interaction has some advantagesstudents apply the function of language learnt, it can be used to have strengthen the social relationship.…”
Section: Lecturer: Yes I Am In Wonderful Chance Thanks So Much Well N...mentioning
confidence: 99%
“…In the studies of various teachers talk agreed that teachers have power in the class to guide their students. However, by using their talks, the teacher may influence students got something new or even to do something (Siregar et al, 2023;Nasmilah, 2023;Meneses et al, 2023;Aas, 2022;Wahyuni et al, 2022;Khusna et al, 2022;Dale et al, 2022;Altamirano et al, 2022;Laoli, 2022;Indriyani et al, 2022;Jayalath, 2021;Karuniasih et al, 2021;Rahayu & Syahrizal, 2020;Herviani, 2020;Buma & Nyamupangedengu, 2020;Yamin et al, 2020;Jin & Webb, 2020;Fitriati et al, 2020;Suciati, 2019;Chase et al, 2019;Iswara et al, Huriyah & Agustiani, 2018;Alijani & Barjesteh, 2018;Jing & Jing, 2018;Glover, 2018;Veen et al, 2017;Biesta et al, 2017;Basra & Thoyyibah, 2017;Stanley & Stevenson, 2017;Nurpahmi, 2017;Kurniawati & Fitriati, 2017;Cao, 2016;Maghfiroh & Nugroho, 2015;Pujiastuti, 2014;Rezaee & Farahian, 2012). On the other hand, the studies of various classroom interaction deal with teachers as a central for how teaching learning process looked like and running well (Harjanto et al, 2022;Cherng et al, 2022;Bukari et al, 2022;Widyasari & Dardjito, 2022;Ayunda et al 2021;…”
Section: Introductionmentioning
confidence: 99%